2003
DOI: 10.1203/01.pdr.0000041513.93422.c8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neonatal High-Dose Short-Term Glucocorticoid Treatment on the Lung: A Morphologic and Morphometric Study in the Rat

Abstract: Glucocorticoids are often applied in neonatology and perinatology to fight the problems of respiratory distress and chronic lung disease. There are, however, many controversies regarding the adverse side effects and long-term clinical benefits of this therapeutic approach. In rats, glucocorticoids are known to seriously impair the formation of alveoli when applied during the first two postnatal weeks even at very low dosage. The current study investigates short-term and long-term glucocorticoid effects on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…The results also showed that for a specific age (postnatal day 60) the body weight and the lung volume are not correlating (R 2 : 27 9 10 À6 ). However, because a correlation between body weight and lung volume exists throughout lung development (for our rat strain (Tschanz et al 2003)), a similar correlation may or may not exist for the mean acinar volume.…”
Section: Estimationmentioning
confidence: 91%
“…The results also showed that for a specific age (postnatal day 60) the body weight and the lung volume are not correlating (R 2 : 27 9 10 À6 ). However, because a correlation between body weight and lung volume exists throughout lung development (for our rat strain (Tschanz et al 2003)), a similar correlation may or may not exist for the mean acinar volume.…”
Section: Estimationmentioning
confidence: 91%
“…Steroids can affect pulmonary vascular development, through the regulation of vasoactive mediators, 20 remodeling of vascular walls, 15,27 and maturation of capillary loops. 3 Also architectural changes to the air-blood barrier can be induced. As the alveolar walls become thinner, the double layered capillaries fuse.…”
Section: Discussionmentioning
confidence: 99%
“…As the alveolar walls become thinner, the double layered capillaries fuse. Tschanz et al 3 studied rat pups that were exposed in utero to dexamethasone, born at term and which eventually were evaluated in the first 4 days after birth, an acceleration of microvascular maturation, resulting in formation of single capillary network septa. Haworth reported that, within 30 min after birth, the endothelial cells, which in the fetal state are cuboidal and bulge into the lumen, flatten.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Finally, GCs enhance the structural maturation of lung capillaries. 11 Although the importance of GC for all of the above processes has been 1 Physiology and Experimental Medicine, The Hospital for Sick Children, Toronto, Ontario, Canada. established, the exact mechanisms of GC mediated enhancement of lung maturation remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%